2020
DOI: 10.1002/lio2.510
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus and auditory cortex; Using adapted functional near‐infrared‐spectroscopy to expand brain imaging in humans

Abstract: Objectives Phantom sound perception (tinnitus) may arise from altered brain activity within auditory cortex. Auditory cortex neurons in tinnitus animal models show increased spontaneous firing rates. This may be a core characteristic of tinnitus. Functional near‐infrared spectroscopy (fNIRS) has shown similar findings in human auditory cortex. Current fNIRS approaches with cap recordings are limited to ∼3 cm depth of signal penetration due to the skull thickness. To address this limitation, we present an innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…According to the neurovascular coupling mechanism, the increase of regional cerebral blood oxygen reflects the activity of neurons. Previous studies have found that auditory cortical activity was increased in tinnitus subjects during silence, whereas this activity was suppressed during broadband noise auditory stimulation [51]. In our study, the concentration of HbO2 in the silence period was higher than that in the sound period, which may also be related to the inhibition of auditory cortical activity by sound stimulation.…”
Section: Discussionsupporting
confidence: 51%
“…According to the neurovascular coupling mechanism, the increase of regional cerebral blood oxygen reflects the activity of neurons. Previous studies have found that auditory cortical activity was increased in tinnitus subjects during silence, whereas this activity was suppressed during broadband noise auditory stimulation [51]. In our study, the concentration of HbO2 in the silence period was higher than that in the sound period, which may also be related to the inhibition of auditory cortical activity by sound stimulation.…”
Section: Discussionsupporting
confidence: 51%
“…Noise‐exposure used to induce tinnitus in the present study resulted in a permanent threshold shift at frequencies adjacent to the noise‐exposure frequency. Accordingly, long‐term sensory damage/deprivation is likely to initiate compensatory homeostatic mechanisms generally seen as increased spontaneous and driven activity, bursting and cross‐connectivity in cochlear nucleus, inferior colliculus, auditory thalamus and auditory cortex (Bauer et al., 2008; Brozoski et al., 2002; Henton & Tzounopoulos, 2021; McGill et al., 2022; Noreña & Farley, 2013; Roberts et al., 2010; Sedley, 2019; Shore & Wu, 2019; Zhai et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Noise-exposure used to induce tinnitus in the present study resulted in a permanent threshold shift at frequencies adjacent to the noise-exposure frequency. Accordingly, long-term sensory damage/deprivation is likely to initiate compensatory homeostatic mechanisms generally seen as increased spontaneous and driven activity, bursting and cross-connectivity in cochlear nucleus, inferior colliculus, auditory thalamus and auditory cortex (Brozoski et al ., 2002; Bauer et al ., 2008; Roberts et al ., 2010; Noreña & Farley, 2013; Sedley, 2019; Shore & Wu, 2019; Henton & Tzounopoulos, 2021; Zhai et al ., 2021; McGill et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%